2020
DOI: 10.1002/ptr.6720
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany, ethnopharmacology, phytochemistry, biological activities and toxicity of Pistacia chinensis subsp. integerrima: A comprehensive review

Abstract: Pistacia chinensis subsp. integerrima (J. L. Stewart ex Brandis) Rech. F. is a valuable medicinal plant used in south Asian communities for the treatment of asthma, diarrhea, diabetes, liver diseases, fever, pain and inflammation. This review critically evaluates the available information on P. integerrima's ethnobotany, ethnopharmacology, phytochemistry, pharmacology and toxicology. Electronic databases such as Google Scholar, PubMed, Springer Link, and so forth, books and theses were used to find relevant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In a recent meta-analysis of randomized, controlled-feeding clinical studies, Fogacci et al [ 56 ] reviewed the effect of pistachio on brachial artery diameter and flow-mediated dilatation and suggested a significant effect of pistachios on endothelial reactivity, affecting brachial artery diameter but not flow-mediated dilatation. Recently, a comprehensive review [ 57 ] and several systematic reviews and meta-analyses Ghanavati et al [ 58 ] demonstrated that pistachio consumption can elicit a beneficial effect on some cardiometabolic risk factors, and Asbaghi et al [ 59 ] suggest the efficacy of pistachio consumption to reduce SBP. Finally, early this year, in the latest review dealing with the effect of dietary polyphenols on vascular health, Grosso and coworkers concluded that hypertension is counteracted by a plant-based dietary pattern, including pistachio, for example, since no single food is enough to control hypertension [ 60 ] ( Figure 1 ).…”
Section: Health Benefits Of Pistachio Consumptionmentioning
confidence: 99%
“…In a recent meta-analysis of randomized, controlled-feeding clinical studies, Fogacci et al [ 56 ] reviewed the effect of pistachio on brachial artery diameter and flow-mediated dilatation and suggested a significant effect of pistachios on endothelial reactivity, affecting brachial artery diameter but not flow-mediated dilatation. Recently, a comprehensive review [ 57 ] and several systematic reviews and meta-analyses Ghanavati et al [ 58 ] demonstrated that pistachio consumption can elicit a beneficial effect on some cardiometabolic risk factors, and Asbaghi et al [ 59 ] suggest the efficacy of pistachio consumption to reduce SBP. Finally, early this year, in the latest review dealing with the effect of dietary polyphenols on vascular health, Grosso and coworkers concluded that hypertension is counteracted by a plant-based dietary pattern, including pistachio, for example, since no single food is enough to control hypertension [ 60 ] ( Figure 1 ).…”
Section: Health Benefits Of Pistachio Consumptionmentioning
confidence: 99%
“…52 Pistacia chinensis Bunge: The fruits of this species are traditionally used in liver diseases and were found to be effective in fatty liver experimentally. 53 Pluchea indica (L.) Less. : It is known that it is used to protect liver health in traditional medicine.…”
Section: Cassia Obtusifolia (L)hs Irwin and Barnebymentioning
confidence: 99%
“…In most cases, it is the presence of multiple mycochemicals in a plant that exerts a pharmacological effect. At times, it is not easy to assume/hypothesize a single mechanism involved (Ahmad, Almubayedh, et al, 2020). Toxicity , adverse effects , and chronic use ; it's not always about the efficacy and potency for the developed test drugs or products; at times, it is also important to monitor the adverse effects, toxicities, and allergy, etc., particularly with chronic use or at high doses.…”
Section: Literature Reviewmentioning
confidence: 99%